The Phenomenon of Environmental Classics (Philosophical and Methodological Analysis) - Nelya Filyanina (Cхід)
The article is dedicated to the analysis of the phenomenon of environmental classics. It is shown that humanities play a growing role in formation of ecological consciousness of the population, supplementing natural sciences knowledge on the way of raising public environmental awareness and development of integrated system of environmental education. It is manifested in the forms, first, of more active appeal of those who are responsible for environmental education to humanities; second, of direct concern to artists and writers by environmental problems and aspiration to contribute in their solving by available means (eco-music, eco-art, eco- and environmental writing). The phenomenon of formation of environmental classics is considered with the reference to the book "Silent Spring" (Rachel Carson, 1962). It is shown its public and educational significance.